Why Do Workers Dislike Inflation? Wage Erosion and Conflict Costs - Joao Guerreiro; Jonathon Hazell; Chen Lian; Christina Patterson (Institute of Labor Economics (IZA), 2024)
How costly is inflation to workers? Answers to this question have focused on the path of real wages during inflationary periods. We argue that workers must take costly actions ("conflict") to have nominal wages catch up with inflation, meaning there are welfare costs even if real wages do not fall as inflation rises. We study a menu-cost style model, where workers choose whether to engage in conflict with employers to secure a wage increase. We show that, following a rise in inflation, wage catch-up resulting from more frequent conflict does not raise welfare. Instead, the impact of inflation on worker welfare is determined by what we term "wage erosion"—how inflation would lower real wages if workers' conflict decisions did not respond to inflation. As a result, measuring welfare using observed wage growth understates the costs of inflation. We conduct a survey showing that workers are willing to sacrifice 1.75% of their wages to avoid conflict. Calibrating the model to the survey data, the aggregate costs of inflation incorporating conflict more than double the costs of inflation via falling real wages alone.
Keywords: E31; J52; J31; 330; inflation; wages; conflict